The Use of Cultural Character (Baraya) Media Ki Banten in Social Studies Learning to Improve Student Characters (Case Study At Primary School Labschool UPI Serang Campus) - Supriatna, Encep; Susilawati, Susilawati; R, Ita Rustiati; Darmawan, Darmawan (International Conference on Elementary Education, 2020)
This research is motivated by the anxiety felt by parents in the educational process which only relies on cognitive aspects, ignoring the affective aspects, thus making learning less meaningful. As a result it does not produce elementary school children who have good character. This is due to the low understanding of character education. This is where war is. Parents of children to help implement character education are very widespread, but have not yet received interesting examples of learning through media that are loved by children. For this reason, researchers try to use the Culture Character Puppet media (Baraya) in Islamic stories (story telling) to instill good character in elementary school children, especially instilling ethics and manners so that children are expected to follow and identify themselves in accordance with the stories in the learning. The location of the primary school used as the subject in this study was the UPI Pilot Laboratory, Serang Campus, located in Serang City. The research method uses classroom action research by carrying out a series of cycles since starting from planning, implementation, observation and reflection. While the data analysis is carried out by triangulation, member check, audit trial and expert opinion, the conclusions are drawn from the analyzed data